Friendship Patterns Of Muslimah Blessed And Their Relationship With Academic Achievement And Character Forming Of Veil Students: Pola Persahabatan Muslimah Bercadar dan Keterkaitannya dengan Prestasi Akademik dan Pembentukan Karakter Mahasiswi Bercadar - Yusi Trihartono; Isa Anshori (Academia Open, 2021)
This article aims to describe the pattern of Muslim friendship with the veil and its relationship to academic achievement and character building for veiled female students at Muhammadiyah University of Sidoarjo. In this study using the kualitatif fenomenology research method with the research subject of veiled female students both all Faculties and Ma'had at Muhammadiyah University of Sidoarjo. The results obtained from this study are veiled female students at Muhammadiyah University strengthening each other in terms of piety, bound by piety to Allah SWT. The friendship pattern of veiled female students has a close relationship with academic achievement, namely that each other is able to guide and become mentors in achieving better achievements. Through the pattern of friendship that is intertwined with each other, they provide good examples in terms of character so that they are able to instill a solid foundation of Islamic character in the friendship